2002
DOI: 10.1104/pp.020007
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Expression of Arabidopsis Phosphate Transporters

Abstract: Phosphorus deficiency is one of the major abiotic stresses affecting plant growth. Plants respond to the persistent deficiency of phosphate (Pi) by coordinating the expression of genes involved in alleviation of the stress. The high-affinity Pi transporters are among the major molecular determinants that are activated during Pi stress. In this study, using three reporter genes (green fluorescent protein, luciferase, and β-glucuronidase) regulated by two Pi transporter promoters, we have carried out an extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
275
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(299 citation statements)
references
References 45 publications
19
275
0
5
Order By: Relevance
“…Nine PHT1 genes have been identified in Arabidopsis thaliana and 13 in rice (Oryza sativa) (Raghothama, 1999;Goff et al, 2002). Gene expression analysis showed that most PHT1 family members are temporally and spatially upregulated in response to Pi starvation (Karthikeyan et al, 2002;Mudge et al, 2002;Misson et al, 2004;Shin et al, 2004). Their expression patterns extend beyond the root, in line with their roles in both Pi uptake and translocation: crucial functions for maintaining the internal P homeostasis in plants.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nine PHT1 genes have been identified in Arabidopsis thaliana and 13 in rice (Oryza sativa) (Raghothama, 1999;Goff et al, 2002). Gene expression analysis showed that most PHT1 family members are temporally and spatially upregulated in response to Pi starvation (Karthikeyan et al, 2002;Mudge et al, 2002;Misson et al, 2004;Shin et al, 2004). Their expression patterns extend beyond the root, in line with their roles in both Pi uptake and translocation: crucial functions for maintaining the internal P homeostasis in plants.…”
Section: Introductionmentioning
confidence: 78%
“…In summary, there is a regulatory step at the ER whereby PHF1 enables the exit of PTs and phosphorylation by CK2 inhibits it by impeding PT-PHF1 interaction in addition to transcriptional control increasing PT levels in response to low Pi (Karthikeyan et al, 2002;Mudge et al, 2002). The activity of this kinase is affected by Pi supply, because reduced phosphorylation of CK2b3 results in its decreased stability and interaction capacity with CK2a3.…”
Section: A Ck2-integrated Model For Pt Er Exitmentioning
confidence: 99%
“…AtPT1 is another major high-affinity Pi transporter in Arabidopsis whose expression is also highly induced by Pi starvation (Muchhal et al, 1996;Karthikeyan et al, 2002). When hps1 mutation was introduced into the transgenic line carrying an AtPT1-GUS construct through a genetic cross, the expression of AtPT1-GUS was also highly induced under Pi starvation in the lateral roots around the hypocotyl-root junction and the root tips (Supplemental Fig.…”
Section: The Hps1 Mutation Enhances Pi Starvation-induced Gene Expresmentioning
confidence: 99%
“…S1). In this construct, a firefly luciferase (LUC) gene is fused to the promoter of the AtPT2 (AtPht1;4) gene, which encodes a high-affinity Pi transporter (Karthikeyan et al, 2002). Pi deficiency induced the expression of the reporter gene fused to the Pi starvation-responsive AtPT2 promoter.…”
Section: Identification Of the Hps1 Mutantmentioning
confidence: 99%
“…Pi transporters belonging to two major gene families (Pht1 and Pht2) have now been identified for a range of plant species (for review, see Rausch and Bucher, 2002) and have been most extensively studied in Arabidopsis (Arabidopsis thaliana; Muchhal et al, 1996;Mitsukawa et al, 1997;Smith et al, 1997Smith et al, , 2000Okumura et al, 1998;Karthikeyan et al, 2002;Mudge et al, 2002). The members of the gene family that are expressed in roots are typically up-regulated under P deficiency, but the molecular basis of the regulation has not been investigated.…”
mentioning
confidence: 99%